Illustration Images in Muslimah Visual Communication Da’wah Movement on Instagram - Rahina Nugrahani; Muhammad Zaffwan Idris; Arif Ardy Wibowo (Komunikator, 2021)
The rise of various da’wah content on Instagram explains the emergence of Muslimah movement to deliver Islamic messages through social media. Through Instagram, the Muslimah community becomes an agent for transforming Islamic knowledge in carrying out da’wah. This study aims to explain how the illustration artworks produced by the Muslimah community become visual communication media and provide their nuances in da’wah through Instagram. With a virtual ethnographic approach, this research is a qualitative study involving 15 illustrators who are members of the Hijabographic virtual community. This study reveals that the embodiment of the illustration artworks shows distinctive style and shape, which makes the Hijabographic community have its own positioning as a virtual community that produces illustration artworks for da’wah content. As visual communication media, the illustration artworks created by Hijabographic community members contain iconic meanings that emphasize aesthetic principles. The creativity of Hijabographic community members in producing illustration artworks is not an individual phenomenon but a structured cultural system that is adaptive to the demands of technological development. Hijabographic community illustration artworks present a new way of performing da’wah through virtual space.